Volker Schlöndorff's cinema : adaptation, politics, and the "movie-appropriate" - Moeller, Hans-Bernhard (Southern Illinois University Press, 2012)
Volker Schlöndorff's Cinema: Adaptation, Politics and the "Movie-Appropriate" examines the work of major postwar German director Volker Schlöndorff in historical, economic, and artistic contexts. Incorporating a film-by-film, twenty-eight chapter study, Hans-Bernhard Moeller & George Lellis reveal a complexity and formal ambitiousness of Schlöndorff that is comparable to that found in Wenders, Herzog, and Fassbinder. In spite of Schlöndorff's successes with films like The Lost Honor of Katharina Blum and The.